META-ANALYSIS OF THE THERAPEUTIC USE OF DIPYRONE IN DOGS: PHARMACOLOGICAL EFFECTS AND CLINICAL SAFETY - SILVA, I. C.; MAIA, C. A. A.; RAYMUNDO, A. C.; PRATA, M. N. L.; ROMERO, T. R. L.; DUARTE, I. D. G.; MANRIQUE, W. G.; PEREZ, A. C.; BELO, M. A. A. (Ars Veterinaria, 2021)
Dipyrone (metamizole) is well-known for its powerful effect with central and peripheral activity. This meta-analysis involved articles published between 1973 and 2021, revealing that Brazil is the country which most published scientific articles relating the use of dipyrone in dogs, and this drug is widely recommended as an analgesic to control pain in cases of postoperative and cancer. Dipyrone is one of the favorite drugs used in small animal clinic in Brazil, and 12 commercial brands are available to use in dogs at doses among 25 to 50mg/kg for oral, intravenous and intramuscular administration. The effects of dipyrone may be potentiated when used in combination with other analgesic agents such as tramadol. In several studies, the occurrence of vomiting has been observed as an adverse effect, especially when the drug is used during surgical procedures, but metamizole has presented a low potential to cause gastric ulceration. The meta-analysis study of the use of dipyrone in dogs shows the clinical importance of this drug in Brazil, being an effective and safe medication, as long as it is used in the indicated dose of 25 mg/kg.